The missing deposits of South Sulawesi: New sources of evidence for the Pleistocene/Holocene archaeological transition. (December 2022) - Newman, Kim; Hakim, Budianto; Oktaviana, Adhi Agus; Burhan, Basran; McGahan, David; Brumm, Adam
Abstract: The Indonesian island of Sulawesi, located in the 'Wallacean' biogeographical zone at the axis of human migration between the super-continents of Sunda and Sahul, has been linked to many research questions relating to the early movements of humans in the region between the landmasses of Asia and Australia. From an archaeological perspective, South Sulawesi is one of the most intensively investigated parts of Indonesia, although much about the early human story in this region remains unknown. While Pleistocene assemblages are scarce, South Sulawesi contains sites with deposits >50, 000 years old, along with rock art of a broadly similar antiquity. Mid-Holocene assemblages reveal a regionally unique technocomplex known as the Toalean. However, knowledge of how these two cultural periods are related has been obscured by a gap in the archaeological record between c.20, 000–10, 000 years ago. This gap has prevented us from understanding the origins of major developments in stone tool technologies, environmental adaptations, and changes in material culture. Cemented archaeological deposits adhering to cave walls, known as breccias, may prove the solution for researchers interested in these poorly understood time periods. Samples taken from archaeological breccias for radiocarbon dating have shown that the deposits currently missing from the archaeological record can still be found attached to cave walls. These breccias contain archaeological deposits that have been consolidated by calcite precipitation and have remained attached to the walls of caves and rockshelters, while the majority of uncemented deposits were removed from the site by erosion or physical action. The identification of these 'time capsules' affirms environmental conditions did not restrict nor prevent occupation or site formation in South Sulawesi during the early Holocene period, and confirms archaeological breccias are a valid source of archaeological data and should be examined to a greater extent in the future. This paper identifies these missing archaeological deposits by dating material from archaeological breccias at the site, Leang Bulu Bettue, in the Maros Regency of South Sulawesi. It suggests that archaeological breccias are a valid and important source of information for consideration in future research. Highlights: Archaeological breccias contain material dating to time periods missing from excavated archaeological deposit. Human occupation of South Sulawesi persisted through the LGM. Breccia formation and removal coincides with significant climatic events since the LGM.